2021
DOI: 10.3390/nu13103459
|View full text |Cite
|
Sign up to set email alerts
|

A Six-Day, Lifestyle-Based Immersion Program Mitigates Cardiovascular Risk Factors and Induces Shifts in Gut Microbiota, Specifically Lachnospiraceae, Ruminococcaceae, Faecalibacterium prausnitzii: A Pilot Study

Abstract: Cardiovascular disease (CVD) prevalence remains elevated globally. We have previously shown that a one-week lifestyle “immersion program” leads to clinical improvements and sustained improvements in quality of life in moderate to high atherosclerotic CVD (ASCVD) risk individuals. In a subsequent year of this similarly modeled immersion program, we again collected markers of cardiovascular health and, additionally, evaluated intestinal microbiome composition. ASCVD risk volunteers (n = 73) completed the one-wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 58 publications
1
52
0
Order By: Relevance
“…In a correlation analysis between indicator genus and clinical indexes, though there was no significant difference in BMI in MCS versus control patients, the indicator Monoglobus showed significantly negative linkage with BMI. The same negative association was reported in another study in individuals with high atherosclerotic cardiovascular disease risk; however, when low-calorie dietary interventions were performed, atherosclerotic markers improved in a time series study ( 47 ). When mice were orally administered Qing-Xin-Jie-Yu Granule (QXJYG), a Chinese traditional decoction which was proven to be clinically effective for CAD patients, Monoglobus was also significantly elevated ( 71 ).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In a correlation analysis between indicator genus and clinical indexes, though there was no significant difference in BMI in MCS versus control patients, the indicator Monoglobus showed significantly negative linkage with BMI. The same negative association was reported in another study in individuals with high atherosclerotic cardiovascular disease risk; however, when low-calorie dietary interventions were performed, atherosclerotic markers improved in a time series study ( 47 ). When mice were orally administered Qing-Xin-Jie-Yu Granule (QXJYG), a Chinese traditional decoction which was proven to be clinically effective for CAD patients, Monoglobus was also significantly elevated ( 71 ).…”
Section: Discussionsupporting
confidence: 74%
“…In MCS versus controls after correction of age noise, the control indicator Dialister , a genus in the phylum Firmicutes , was significantly depleted in Tibetan coronary heart disease (CHD) patients compared to healthy Tibetans and showed negative associations with lipopolysaccharide (LPS), consistent with its protective anti-inflammation role ( 46 ). Most MCS indicators were found to be from the families Oscillospiraceae and Lactobacillaceae , usually playing favorable roles in CAD patients for production of butyrate ( 47 ). It worth noting that the MCS indicators Monoglobus ( 47 ) and Flavonifractor ( 48 ) were significantly decreased in CAD patients in other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Translating this knowledge into high-precision microbiome-mediated CVD strategies will be a game changer, as current treatments seem to be inadequate in many cases. While more and more modernized approaches dominate the field of CVD therapeutics, we should not by any means underestimate the significant impact of more conventional interventions, such as diet and exercise [177].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been found that Ruminococcaceae is negatively related to inflammatory bowel disease, and Ruminococcaceae is considered as the producer of butyrate, which is the preferred source of energy for colonic epithelial cells and plays an important role in maintaining colon health [26]. It can also retard CKD and CVD by improving lipids and blood pressure [36].…”
Section: Pathophysiological Effects Of Gut Microbiotamentioning
confidence: 99%